The effect of high carbon dioxide content on the performance and emission characteristics of a Direct Injection (DI) compressed natural gas engine - Ayandotun, W.B. (Trans Tech Publications Ltd, 2014)
This paper investigates the potential of utilizing the undeveloped natural gas fields in Malaysia with high carbon dioxide (CO2) content ranging from 28 to 87. For this experiment, various CO2 proportions by volume were added to pure natural gas as a way of simulating raw natural gas compositions in these fields. The experimental tests were carried out using a 4-stroke single cylinder spark ignition (SI) direct injection (DI) compressed natural gas (CNG) engine. The tests were carried out at 180oCA BTDC injection timing and 3000 rpm, to establish the effects on the engine performance. The findings revealed that the brake torque decreased by 9 with 20 CO2 proportion in the mixture due to the decrease in the heating value of the mixture. At the same proportion of CO2, the brake specific fuel consumption decreased by about 8.5 and the brake thermal efficiency increased by 9.2. There was a reduction in the unburnt hydrocarbons (THC) and carbon monoxide (CO) emissions by 15 and 89 respectively, but the NOx emissions increased by 78. The utilization of natural gas with 20 CO2 content as fuel in DI-CNG engine was found to be viable with insignificant drop in engine performance and with reductions in exhaust emissions. Â© (2014) Trans Tech Publications, Switzerland.